Environmental Barriers To Transfer And Commercialize Nanomedicine Research Results In Iran: A Qualitative Research - Seyed Reza Hejazi; Payam Mansoor Hosseini (Tehran University of Medical Sciences, 2014)
Background and Aim: Nanomedicine is growing very fast. Transfer and commercialization of research results in Nanomedicine is a missing link between technology and market. This is affected by some factors which are barriers to commercialization. The aim of this study was to identify barriers to transfer and commercialize nanomedicine research results in Iran. Materials and Methods: The research method was qualitative method based on eight semi-structured in-depth interviews with nanomedicine and commercialization experts in year 2011 in Iran.  Results: The proposed model of commercialization consisted of five distinct parts: transferor, transferee, transfer object, transfer mechanisms and environmental factors. In this study twenty six environmental factors in seven categories as Environmental Barriers to Transfer and Commercialization of Nanomedicine Research Results was identified. Conclusion: The most important barrier to nanomedicine commercialization in Iran are licensing system, lack of capital, and consumption culture.